In situ multiple sulfur isotope analysis by SIMS of pyrite, chalcopyrite, pyrrhotite, and pentlandite to refine magmatic ore genetic models - LaFlamme, C.; Martin, L.; Jeon, H.; Reddy, Steven; Selvaraja, V.; Caruso, S.; Bui, T.; Roberts, M.; Voute, F.; Hagemann, S.; Wacey, D.; Littman, S.; et al. (Elsevier Science BV, 2016)
With growing interest in the application of in situ multiple sulfur isotope analysis to a variety of mineral systems, we report here the development of a suite of sulfur isotope standards for distribution relevant to magmatic, magmatic-hydrothermal, and hydrothermal ore systems. These materials include Sierra pyrite (FeS2), Nifty-b chalcopyrite (CuFeS2), Alexo pyrrhotite (Fe(1 −x)S), and VMSO pentlandite ((Fe,Ni)9S8) that have been chemically characterized by electron microprobe analysis, isotopically characterized for δ33S, δ34S, and δ36S by fluorination gas-source mass spectrometry, and tested for homogeneity at the micro-scale by secondary ion mass spectrometry. Beam-sample interaction as a function of crystallographic orientation is determined to have no effect on δ34S and Δ33S isotopic measurements of pentlandite. These new findings provided the basis for a case study on the genesis of the Long-Victor nickel-sulfide deposit located in the world class Kambalda nickel camp in the southern Kalgoorlie Terrane of Western Australia. Results demonstrate that precise multiple sulfur isotope analyses from magmatic pentlandite, pyrrhotite and chalcopyrite can better constrain genetic models related to ore-forming processes. Data indicate that pentlandite, pyrrhotite and chalcopyrite are in isotopic equilibrium and display similar Δ33S values + 0.2‰.This isotopic equilibrium unequivocally fingerprints the isotopic signature of the magmatic assemblage. The three sulfide phases show slightly variable δ34S values (δ34Schalcopyrite = 2.9 ± 0.3‰, δ34Spentlandite = 3.1 ± 0.2‰, and δ34Spyrrhotite = 3.9 ± 0.5‰), which are indicative of natural fractionation. Careful in situ multiple sulfur isotope analysis of multiple sulfide phases is able to capture the subtle isotopic variability of the magmatic sulfide assemblage, which may help resolve the nature of the ore-forming process. Hence, this SIMS-based approach discriminates the magmatic sulfur isotope signature from that recorded in metamorphic- and alteration-related sulfides, which may not be resolved during bulk rock fluorination analysis. The results indicate that, unlike the giant dunite-hosted komatiite systems that thermo-mechanically assimilated volcanogenic massive sulfides proximal to vents and display negative Δ33S values, the Kambalda ores formed in relatively distal environments assimilating abyssal sulfidic shales.